WIZERUNEK MEDIALNY DONALDA TRUMPA WEDŁUG MODELI KOMUNIKACJI - Jankiewicz, Adam (Scripta Neophilologica Posnaniensia, 2019)
The article brings closer various ways in which the president of United States Donald Trump image is presented in mass media, especially in the world press. The positive as well as the negative Donald Trump’s image is created and communicated to their receivers in accordance with models of communication such as: the mathematical model of communication as a process by Shannon and Weaver (1949) and the interpersonal model of communication DRAAM (domain-resource-agent-access-management) created by Puppel (2004). The article concentrates on the management of information and creation of media messages using communicative resources in which way to achieve anticipated reaction of the receiver to the featured image.